A lei de Thirlwall multissetorial : uma proposta alternativa de análise a partir da relação bilateral Brasil-China - Santos, Helenise Sarno (2014)
According to Thirlwall (1979), the long-term growth of a country depends on income - elasticities of exports and imports. The debate over this law has evolved into a multi-sectoral approach, as developed by Araujo and Lima (2007). According to these authors, the industry analysis possible to identify one(s) Sector(s) that can(m) contribute relatively more in the country\'s growth strategy, it suffices that prioritizes Sector(s) with most(es) reasons of income elasticities of exports when compared to the income elasticity of imports. The demonstrating the feasibility of a strategy of export-led growth to sectors that have higher income elasticity, as they are considered the most dynamic sectors to Thirlwall. The hypothesis is that the low economic growth is associated with the international insertion strategy, external trade, which is highly concentrated in branches whose income elasticity of exports are relatively low. To achieve the goal and test the hypothesis launched estimations with annual data from Brazilian states for the period 1999-2009 are performed using the methodology of panel data. The results confirmed that the manufacturing sector has the highest ratio of elasticities, which implies that a change in the long-term growth strategy that prioritizes this sector reduces the output gap relative to the Chinese economy. However, it is believed that the country would return to the manufacturing sector is not enough, one must prioritize dynamic subsectors towards Verdoorn-Kaldor-Thirlwall, should stimulate those subsectors that simultaneously create jobs, contribute to the growth of output and productivity, without compromising the balance of payments, leading the Brazilian economy to a virtuous circle of long-term growth through a process of cumulative causation with structural change. It is believed that these sub-sectors of industry identified by empirical analysis should be prioritized to improve the long-term growth of Brazilian economy.